Mini Gold Nanorods with Tunable Plasmonic Peaks beyond 1000 nm - Chang, Huei-Huei (Chemistry of materials : a publication of the American Chemical Society, 2018)
Gold nanorods of small sizes have larger absorption cross sections and higher photothermal efficiency compared to larger ones. However, tuning the surface plasmon resonance of small gold nanorods remains a challenge because increasing an aspect ratio usually results from increasing dimensions. We demonstrate the synthesis of mini gold nanorods with tunable longitudinal surface plasmon resonance from ~600 to >1300 nm accompanied by precise control over widths <10 nm. Two weak reducing agents, ascorbic acid and even milder hydroquinone, were applied to a seed-mediated growth method to tune the aspect ratios of mini gold nanorods from 2.2 to 10.8 corresponding to average dimensions 19.3 × 9.0 nm through 93.1 × 8.7 nm, respectively. This seed-mediated growth of mini gold nanorods results in an average 96% of rods and yields of at least 79% based on gold ion reduction. The extinction coefficients of mini gold nanorods were established based on the gold content from inductively coupled plasma mass spectrometry. The longitudinal extinction coefficients range from 1.6 × 108 to 1.4 × 109 M-1 cm-1 depending on aspect ratio. We show that liter-scale mini gold nanorod syntheses are reproducible, and the dimensions, aspect ratios, and shape percent yields are comparable to those of a small-scale synthesis